Enhancing heat transport in multiphase Rayleigh–Bénard turbulence by changing the plate–liquid contact angles. (25th February 2022) - Liu, Hao-Ran; Chong, Kai Leong; Ng, Chong Shen; Verzicco, Roberto; Lohse, Detlef
Abstract: Abstract : This numerical study presents a simple but extremely effective way to considerably enhance heat transport in turbulent wall-bounded multiphase flows, namely by using oleophilic walls. As a model system, we pick the Rayleigh–Bénard set-up, filled with an oil–water mixture. For oleophilic walls, using only 10 % volume fraction of oil in water, we observe a remarkable heat transport enhancement of more than 100 % as compared to the pure water case. In contrast, for oleophobic walls, the enhancement is only of about 20 % as compared to pure water. The physical explanation of the heat transport increment for oleophilic walls is that thermal plumes detach from the oil-rich boundary layer and carry the heat with them. In the bulk, the oil–water interface prevents the plumes from mixing with the turbulent water bulk and to diffuse their heat. To confirm this physical picture, we show that the minimum amount of oil necessary to achieve the maximum heat transport is set by the volume fraction of the thermal plumes. Our findings provide guidelines of how to optimize heat transport in wall-bounded thermal turbulence. Moreover, the physical insight of how coherent structures are coupled with one of the phases of a two-phase system has very general applicability for controlling transport properties in other turbulent wall-bounded multiphase flows.